Superior Capsular Reconstruction Using 3-layered Fascia Lata Autograft Reinforced with a Nonresorbable Suture Mesh - Martin Polacek, M.D., Ph.D; Cecilie P. Nyegaard, M.D (Elsevier, 2020)
Purpose: The purpose of this study was to evaluate the short-term clinical outcomes and the complications related to arthroscopic superior capsular reconstruction (SCR) using a 3-layered fascia lata autograft (FLA) reinforced with a nonresorbable suture mesh, in the treatment of irreparable massive rotator cuff tears (MRCTs). Methods: Consecutive patients with irreparable MRCTs (Goutallier 4, Hamada grade 1-2, Bateman 3-4) who were treated with arthroscopic SCR using reinforced FLA in 2018 were included. Patients with an irreparable subscapularis/infraspinatus, serious cardiovascular condition, systemic infection, rheumatic disease, and known alcohol/drug abuse were excluded from the study. Range of motion and Shoulder Pain and Disability Index (SPADI) scores were assessed preoperatively, at 6 months, and at 12 months postoperatively. A simple t test was used to compare the outcomes. P values <.05 were considered significant. Complications and revision surgeries were registered. Results: A total of 24 consecutive patients (15 males, 9 females) with a mean age of 61 years (range, 41-76) were enrolled. Twenty (83%) patients achieved minimal clinically important difference in the SPADI score (>18) and 14 (58%) experienced substantial clinical benefit in SPADI (>45). The mean SPADI score improved from 59.0 to 9.7 (P < .0001) at 1-year follow-up. Active abduction improved from 59.5° to 154.3° (P < .0001) and active forward flexion improved from 67.0° to 160.3° (P < .0001) at 1-year follow-up. Eighteen (75%) patients achieved substantial clinical benefit in active abduction (>28.5°) and active forward flexion (>35.4°). Complications included progression of osteoarthritis in 2 cases, tear of the graft in 1 case, and pullout of the anchor in another. Two patients experienced donor site morbidity after harvesting the fascia lata autograft. Conclusions: Eighty-three percent of the patients achieved minimal clinically important difference and were successfully treated with arthroscopic SCR using a FLA reinforced with a suture mesh. The procedure had a complication rate of 17% and 8.5% of the patients experienced donor site morbidity. All complications occurred in patients who were previously treated with an attempted rotator cuff repair. Level of Evidence: Level IV, therapeutic case series.